Paving the way - Chew, Pei Shwen (2017)
This paper presents Paving the Way, a knowledge-centric campaign on path-sharing by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Path-sharing is a budding concept within footpath usage emphasising mutual safe and gracious behaviour among footpath users. Paving the Way targets secondary students in Singapore aged 13 to 17, addressing their lack of knowledge about proper path-sharing behaviour and aiming to raise awareness about it, through explaining its importance and how to perform such behaviour. To address current knowledge gaps regarding path-sharing etiquette, qualitative and quantitative research was carried out to explore the path usage habits of students in Singapore. Based on research findings, key messages and campaign strategies of “storytelling”, “raising risk perception”, “raising self-efficacy” and “gamification” were crafted. These guided specific campaign tactics, including a web comic series about path-sharing, amongst other online content on our Instagram page. Roadshows were held in nine secondary schools, with games designed around recommended path-sharing behaviour. The on-ground outreach, conducted from January to March 2017, was highly successful. Thereafter, post-campaign research, comprising a post-roadshow questionnaire and a retention test, was carried out to evaluate the campaign’s effectiveness in achieving its objectives. Subsequently, key achievements and limitations of the campaign are discussed. This is followed by sustainability initiatives aimed at continuation of this campaign—specifically with students from Evergreen and Dunman Secondary. Original documents, including campaign collaterals, event photographs and relevant data, have been included in the appendices as references to the main paper.